Copper(I) and Silver(I) Complexes of 1, 3‐Diphosphacyclobutadiene Sandwich Anions: Synthesis, Crystal Structures, and Solution and Solid‐State NMR Spectroscopic Characterization. Issue 10 (5th December 2013) - Malberg, Jennifer; Wiegand, Thomas; Eckert, Hellmut; Bodensteiner, Michael; Wolf, Robert
Abstract: 1, 3‐Diphosphacyclobutadiene complexes have previously been employed as metalloligands to a few transition metals such as tungsten, cobalt, rhodium, platinum, and gold. Here, we describe the synthesis and the structural and spectroscopic characterization of novel copper(I) and silver(I) complexes with the sandwich anions [Co(η 4 ‐P2 C2 R2 )2 ] – (R = t Bu or t Pent). Reactions of [K(thf)3 Co(P2 C2 t Pent2 )2 ] and [K(thf)2 Co(P2 C2 t Bu2 )2 ] with CuCl(PPh3 )/PPh3 yielded mononuclear copper(I) complexes [CuCo(P2 C2 R2 )2 (PPh3 )2 ] [R = t Pent (1 ), t Bu (2 )]. The salt [Cu(PMe3 )4 ][Co(P2 C2 t Pent2 )2 ] (3 ), which consists of a [Cu(PMe3 )4 ] + cation and a noncoordinated [Co(P2 C2 t Pent2 )2 ] – anion, was obtained when [K(thf)3 Co(P2 C2 t Pent2 )2 ] was treated with CuCl(PPh3 ) in the presence of an excess amount of PMe3 . Salt metathesis of [K(thf)3 Co(P2 C2 t Pent2 )2 ] with AgCl and AgSbF6 in the presence of PMe3 afforded novel silver(I) complexes [AgCo(P2 C2 t Pent2 )2 (PMe3 )3 ] (4 ), [AgCo(P2 C2 t Pent2 )2 (PMe3 )2 ] (5 ), and [Ag2 Co(P2 C2 t Pent2 )2 (PMe3 )5 ]SbF6 (6 ). The molecular structures of1, 2, 5, and6 were determined by X‐ray crystallography. The solution behavior of1 –6 was analyzed by variable‐temperature 1 H, 31 P 1 H, and 13 C 1 H NMR spectroscopy in [D8 ]THF. 31 P solution and solid‐state NMR spectra, aided by two‐dimensional dipolar and/or J ‐based correlation spectroscopy, support the proposed structures and allowed the compositions of polycrystalline precipitated products to be analyzed. Furthermore, characteristic 31 P chemical shifts and indirect spin–spin coupling constants offer a clear distinction between different bonding patterns realized in this class of compounds. Abstract : The sandwich [Co(η 4 ‐P2 C2 R2 )2 ] – (R = t Bu or t Pent) acts as a metalloligand in new copper(I) and silver(I) complexes, which are additionally stabilized by tertiary phosphanes PPh3 or PMe. The complexes show monomeric solid‐state structures with up to two coordinated metal cations. Solid‐state 31 P and 13 C NMR spectroscopy is a powerful tool for the characterization of these compounds.